2002
DOI: 10.1142/s0218127402006254
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evidence for Spatiotemporal Stability and Control of a One-Way Open CML

Abstract: We present an experimental evidence for spatiotemporal stability of a real one-way open coupled map lattice implemented by electronic circuits. Furthermore, it is shown that the decentralized delayed feedback control method can suppress the spatial instability and the spatiotemporal chaos in the coupled map lattice circuits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2002
2002

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Konishi, Kokame and Hirata reported that the decentralized delayed feedback control (DDFC) method can stabilize chaotic behavior in a one-way open CML [Konishi et al, 1998[Konishi et al, , 2000a. Imai et al observed the instability in the electronic CML circuits, and demonstrated the suppression of the instability by the DDFC method [Imai et al, 2002]. Konishi et al [2000b] verified that the mechanism of the spatial instability in the CML can be extended to continuoustime systems.…”
Section: Introductionmentioning
confidence: 98%
“…Konishi, Kokame and Hirata reported that the decentralized delayed feedback control (DDFC) method can stabilize chaotic behavior in a one-way open CML [Konishi et al, 1998[Konishi et al, , 2000a. Imai et al observed the instability in the electronic CML circuits, and demonstrated the suppression of the instability by the DDFC method [Imai et al, 2002]. Konishi et al [2000b] verified that the mechanism of the spatial instability in the CML can be extended to continuoustime systems.…”
Section: Introductionmentioning
confidence: 98%